A contrastive analysis of English and Chinese intonation systems: an auto-segmental metrical framework - Yap, Ngee Thai; Yahya, Yasir; Ng, Chwee Fang; Qingbo, Tian (Foreign Language Teaching & Research Press, 2024)
Intonation refers to the use of super-segmental features to convey pragmatic meanings at the sentence level in a linguistically structured way. The difference in intonation between the native language and a foreign language may influence second language learners’ acquisition of intonation. The purpose of this study is to explore the similarities and differences at the level of phonological representation between English and Chinese intonation systems. This study investigated English and Chinese intonation systems, respectively, from both form and meaning under the Auto-segmental Metrical framework by referring to previous studies and illustrating examples. The results showed that in terms of form, there were notable differences in the structural elements and their inventories between the intonation systems of English and Chinese. In terms of meaning, assertions were represented by different structural elements in English and Chinese intonation systems; the types of structural elements in English intonation possessed the capability to convey complex and subtle meanings, contrasting with the comparatively simpler nature of Chinese intonation. The results indicate the potential effects of Chinese intonation on the acquisition of English intonation by Chinese learning English as a foreign language and provide evidence for explaining the challenges that they face in learning English intonation.